The Proximate Analysis and Nutrition Assessment of Catfish Flour Produced by Different Drying Time and Temperature - Restuti, Arisanty Nursetia; Jannah, M; Fitriyah, D; Yulianti, A; Rahmawati, D; Ahmad, A; Gemaputri, A A; Kinanti, L A B (International Journal of Technology, Food and Agriculture, 2025)
Catfish (Clarias sp.) is a type of freshwater fish that people often consume because of its high nutritional value, deliciousness, and affordability. However, catfish products are often damaged due to high water content. Production of catfish flour is an alternative to make catfish products more durable and easier to diversify. The objective of this study is to determine the proximate and nutritional content of catfish flour produced using different drying times (duration) and temperatures. This study used an experimental laboratory method with two treatment factors, namely drying temperature consisting of 2 levels (60°C and 150°C) and drying time (duration) consisting of 2 levels (36 hours and 3 hours). The result showed the proximate and nutrition content of catfish flour with a drying temperature of 60°C and duration of 36 hours was fat 17.3402%, protein 83.9166%, water 9.8682%, ash 4.7125%, Fe 0.0157%, Ca 0.0602%, Zn 0.0029%. While the proximate and nutrition content of catfish flour with a drying temperature of 150°C and duration of 3 hours was fat 22.0204%, protein 85.9741%, water 6.1044%, ash 4.2682%, Fe 0.0022%, Ca 0.1073%, Zn 0.0032%. This finding reveals that drying temperature and time affected catfish flour's proximate and nutrition content.